The Disclosure of Sexual Assault on Social Media in Indonesia: A Criminal Law Perspective - Anggun Anugrah, Tirana; Izza Elvany, Ayu (KnE Social Sciences, 2023)
This study aimed to determine the factors that contribute to the prevalence of people speaking up and claiming to be victims of sexual assault, as well as to determine whether speaking up on social media is criminal defamation. This empirical legal research analyzed the issue by using sociological and victimological approaches. The results of this study showed that the factors which cause the ’victims’ to speak up on social media for sexual harassment they have experienced comprised of awareness, mental readiness that manifested into psychological resilience, lack of knowledge of the law and means of filing reports, the culture of victim-blaming, difficulties in proof, benefits to others, a desire to receive an apology from the perpetrator and a sense of justice. Furthermore, if the sexual assault could not be proven, speaking up on social media raised the possibility of being reported by the alleged perpetrators for criminal defamation under Article 27, paragraph 3 of Law Number 19 of 2016 on the Amendment of Law Number 11 of 2008 on Information and Electronic Transactions. Keywords: Criminal Defamation, Sexual Assault, Social Media